2018
DOI: 10.3390/molecules23051113
|View full text |Cite
|
Sign up to set email alerts
|

A 3D-QSAR Study on the Antitrypanosomal and Cytotoxic Activities of Steroid Alkaloids by Comparative Molecular Field Analysis

Abstract: As part of our research for new leads against human African trypanosomiasis (HAT), we report on a 3D-QSAR study for antitrypanosomal activity and cytotoxicity of aminosteroid-type alkaloids recently isolated from the African medicinal plant Holarrhena africana A. DC. (Apocynaceae), some of which are strong trypanocides against Trypanosoma brucei rhodesiense (Tbr), with low toxicity against mammalian cells. Fully optimized 3D molecular models of seventeen congeneric Holarrhena alkaloids were subjected to a comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…Related compounds from the stembark, Conessimine (0.17 ± 0.08) 19 ; isoconessimine (0.17 ± 0.11) 20 ; conessine (0.42 ± 0.09) 21 ; and holarrhesine (0.12 ± 0.08) 22 also showed very high antitrypanosomal activity, with high selectivity to the parasites [selectivity index (SI) >100] compared to mammalian L6 cells (Nnadi et al, 2017 ). A 3D-Quantitave Structure Activity Relationship (QSAR) study revealed that steric activity around the C-3 amino group tends to increase activity, while steric activity in the vicinity of the amino group of the pyrroline/pyrrolidine rings and the C-17β-acetyl or C-20 methyl groups tended to decrease activity (Nnadi et al, 2018 ). Following on from this, the active aminosteroids together with 22 , 3α- dihydroholaphyllamine ( 23 ), and holarrhetine ( 24 ) were also tested on animal trypanosome species using resazurin-based in vitro screening assay in our lab (Nnadi et al, 2019 ).…”
Section: Active Compounds From Nigerian Plantsmentioning
confidence: 99%
“…Related compounds from the stembark, Conessimine (0.17 ± 0.08) 19 ; isoconessimine (0.17 ± 0.11) 20 ; conessine (0.42 ± 0.09) 21 ; and holarrhesine (0.12 ± 0.08) 22 also showed very high antitrypanosomal activity, with high selectivity to the parasites [selectivity index (SI) >100] compared to mammalian L6 cells (Nnadi et al, 2017 ). A 3D-Quantitave Structure Activity Relationship (QSAR) study revealed that steric activity around the C-3 amino group tends to increase activity, while steric activity in the vicinity of the amino group of the pyrroline/pyrrolidine rings and the C-17β-acetyl or C-20 methyl groups tended to decrease activity (Nnadi et al, 2018 ). Following on from this, the active aminosteroids together with 22 , 3α- dihydroholaphyllamine ( 23 ), and holarrhetine ( 24 ) were also tested on animal trypanosome species using resazurin-based in vitro screening assay in our lab (Nnadi et al, 2019 ).…”
Section: Active Compounds From Nigerian Plantsmentioning
confidence: 99%
“…Clearly, there is a need to explore this for further development. Following our previous findings on lead identification and subsequent refinement of the quantitative structure-antitrypanosomal (QSAR)/cytotoxic activities relationship of steroid alkaloids from Holarrhena africana (Apocynaceae) against T. brucei species and L6 mammalian myoblast [16], there is a need to further study their activities against AAT-causing trypanosomes, including their mode of trypanocidal activity and whether cross-resistance with diminazene is likely to occur.…”
Section: Introductionmentioning
confidence: 99%
“…The antimicrobial actions of natural compounds are usually complex and the reported cellular or biochemical effects are often not the primary causes of phenotypic observations, due to the compounds interacting with off-target proteins and multiple targets [18,19,20], especially in trypanosomatids, which are characterized by complex and unusual biochemical processes [21]. However, such mechanistic studies are necessary to give further insights into their antitrypanosomal action, which, supplemented with the theoretical findings on 3D-QSAR [16], may be used to optimize such compounds from hits to leads and further on to new and specific drugs. Thus, the compound’s potency, its target within the parasites’ physiology and the potential to withstand the development of resistance, especially cross-resistance with the existing set of drugs, have all to be considered to identify and develop new antiparasite chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…The target compound (tR 5.39 min, [M + H] + : m/z 497.4116, [M + 2H] 2+ : m/z 249.2087) was accompanied by small amounts of two congeneric alkaloids with [M + H] + at m/z 415 and 485 constituting about 3.9 and 4.9% (tR 3.77 and 5.13 min, Figure 3 ), as estimated by integration of extracted ion chromatograms for the respective [M + 2H] 2+ ions. The former of these impurities was unambiguously identified as unesterified cyclovirobuxeine-B by its exact mass ([M + H] + : m/z 415.3731, calcd for C 27 H 47 N 2 O + 415.3738; [M + 2H] 2+ : m/z 208.1923) and by comparison to authentic reference compound [ 13 , 14 ] The formation of this compound in small quantities by hydrolysis of 1 during the workup and isolation process cannot be excluded. The latter displayed an [M + H] + at m/z 485.4179 corresponding to C 31 H 53 N 2 O 2 + ([M + 2H] 2+ at 243.2134).…”
Section: Methodsmentioning
confidence: 99%